"42nd" and "The Heights:" A Century Long Romance. (3rd April 2022) - Horbal, Bogdan
ABSTRACT: The New York Public Library was created in 1895, the same year Columbia's Low Library opened its doors on the new campus in Morningside Heights. From that time on, the two institutions engaged in formal and informal cooperation in collection development and have been viewed as either complementary resources or even one resource. There were numerous individuals who, while being affiliated with one of these institutions, were also readers at the other institution or even impacted the other institution through their activities. The present essay highlights foundational interactions between the NYPL and Columbia University that had an enduring impact in the field of Slavic, East European, and Eurasian studies.